2018
DOI: 10.1002/jcb.28107
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Downregulation of fibroblast growth factor 5 inhibits cell growth and invasion of human nonsmall‐cell lung cancer cells

Abstract: The morbidity and mortality rates of nonsmall‐cell lung cancer (NSCLC) have increased in recent years. We aimed to explore the biological role of fibroblast growth factor 5 (FGF5) in NSCLC. We first established that the expression of FGF5 was increased in NSCLC tissues compared with the normal adjacent tissues. The expression of FGF5 was also increased in NSCLC cell lines. The effect of FGF5 silencing on cell proliferation, cell cycle, apoptosis, migration, and invasion of H661 and CALU1 cells was then examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…High FGF5 expression was an independent prognostic factor for patients, and was associated with worse overall survival and relapse-free survival in lung adenocarcinoma patients. Zhou et al ( 22 ) revealed that FGF5 expression was aberrantly increased in NSCLC tissues and cell lines. The inhibition of FGF5 significantly suppressed NSCLC cell line proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…High FGF5 expression was an independent prognostic factor for patients, and was associated with worse overall survival and relapse-free survival in lung adenocarcinoma patients. Zhou et al ( 22 ) revealed that FGF5 expression was aberrantly increased in NSCLC tissues and cell lines. The inhibition of FGF5 significantly suppressed NSCLC cell line proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Metzner demonstrated that the inhibition of FGF5 signaling is associated with reduced melanoma cell proliferation, and anchorage-independent growth 20 . Recently, downregulation of FGF5 has been reported to inhibit cell growth and invasion of human non-small-cell lung cancer cells 9 . In osteosarcoma, miR-567 has been found to inhibit cell proliferation, migration, and invasion by targeting FGF5 21 .…”
Section: Discussionmentioning
confidence: 99%
“…FGF5 has been demonstrated oncogenic activity of FGF5 in astrocytic brain tumors and attribute to both autocrine effects on the tumor cells as well as paracrine effects on endothelial cells 8 . Zhou et al have demonstrated that the downregulation of FGF5 inhibited cell growth and invasion of human non-small-cell lung cancer cells 9 . FGF5 expression was found to be significantly upregulated in breast cancer patients relative to that in normal controls ( P < 0.0001), and breast cancer patients in the FGF5 low-expression group were correlated with better clinical characteristics 10 .…”
Section: Introductionmentioning
confidence: 99%
“…FGF5 has been discussed in many other cancers and has multiple roles in cancer development [ 46 , 47 , 48 ]. FGFR1 IIIc and FGFR2 IIIc are considered the preferential receptors for FGF5.…”
Section: Deregulation Of Fgf/fgfr In Hccmentioning
confidence: 99%